EVALUASI EFEKTIVITAS PERAN JABATAN BARU FUNGSIONAL PENYULUH PAJAK - Warsiana Yustianingsih Agustin; Siti Nuryanah (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
The Indonesian tax system employs a self-assessment mechanism, granting taxpayers autonomy to calculate, pay, and disclose their tax obligations. However, this approach may cause opportunities for misuse, deviations, and tax smuggling, resulting in suboptimal taxpayer compliance. This research aims to analyze how counseling activities and the role of new functional position of tax advisor influence the individual taxpayers’ compliance behavior in reporting the Taxpayers’ Annual Tax Return, especially at KPP Pratama Jakarta Matraman. The study is a qualitative study based on Campbell's Effectiveness Theory (1989). Using triangulation data collected from document analysis, surveys and interviews, the findings show that the role of the new functional position of tax advisor is highly effective based on program success criteria, while target success rates are less effective. Overall, Reliable Instructor, Workload, Organizational Support, and Internal Control contribute to a moderate effective rating. Addressing target alignment issues is crucial to enhance counseling's efficacy in improving taxpayer reporting compliance. This study provides practical implications to the tax authority for collaborative counseling implementation, along with improved facilities, to elevate the functional role of tax advisor at KPP Pratama Jakarta Matraman.